An integrative approach to counseling : bridging Chinese thought, evolutionary theory, and stress management - Santee, Robert G. (Multicultural aspects of counseling and psychotherapy., 2007)
An Integrative Approach to Counseling: Bridging Chinese Thought, Evolutionary Theory, and Stress Management offers a global and integrative approach to counseling that incorporates multiple concepts and techniques from both eastern and western perspectives. The book identifies commonalities rather than the differences between them. The book also compares and contrasts the underlying cultural assumptions of western counseling with those of the Chinese perspectives of Confucianism, Daoism, and Buddhism, relative to integrating and applying a more global approach to helping individuals functional.